Initial Activities Encouraging Students’ Autonomous Learning: Faculty Teacher Training and Education Program - Khulaifiyah Khulaifiyah; Utami Widiati; Mirjam Anugerahwati; Nunung Suryati (UIR Press, 2023)
Initial activities become important as the stepstone to raise students’ autonomous level. The study aims to explore lecturers’ initial activities to encourage students’ autonomous learning. Autonomous learning is a process to be apprehensive of taking control of literacy. This study used a case study and a content analysis in the qualitative exploration. The English teacher educators at the English language education department, the faculty of teacher training and education in Pekanbaru became the research samples. A qualitative approach is chosen as exploration design with the help of Nvivo 12 Apps since interviews come as the main instrument. Some interview points questioned how lecturers help learners comprehend the material, determine their particular pretensions, chancing out supporting coffers. The study reveals that the lecturer's exertion as the initial activities were giving the material explanation, giving information about the course figure, giving assignments, giving what students need, giving provocation or motivation, sharing experiences, making personal approach, exercising, being a Model, making agreement letter, warning, having a concession, having references of material, participating gests, checking students’ appreciation by reviewing, giving question and test. Yet, giving assignments collectively or in collaboration, systems or incidental test becomes a proposed exertion in the initial process to enhance learners’ autonomous.